VALUE OF THE USE OF THE AMPUTEE MOBILITY PREDICTOR IN A PRACTICE OF THE PRIMARY PROSTHETICS IN PATIENTS WITH LOWER LIMB STUMPS DUE TO DISEASES OF A VASCULAR NATURE: THE CASE OF PATIENTS WITH UNILATERAL HIP AMPUTATION - Васильченко, Елена Михайловна; Косарев, Владимир Александрович; Жатько, Ольга Валерьевна; Степанова, Елена Юрьевна (Medicine in Kuzbass, 2019)
Rehabilitation of patients following the lower limb amputation is a complex task with the prosthesis as a major procedure. The basic aspects of The Amputee Mobility Predictor as an instrument which allows the prediction of the ability of the disabled persons to move around with a prosthesis and the determination of the level of complexity of prosthetic and orthopaedic appliances being provided were studied. One hundred and fourteen patients who were admitted to the clinic of the FSBI NSPC MSE RDP, Ministry of Labour and Social Protection of the Russian Federation from 20.02.2017 till 20.04.2018 for primary prosthesis following hip amputation due to peripheral artery disease were examined. Findings demonstrate the perspectivity of usage of The Amputee Mobility Predictor in terms of prediction and evaluation of the effectiveness of rehabilitation interventions.